Neural Processing of Other-Race Faces as a Function of Racial Familiarity: A P300 Study - Yan Shan, Tai; Reza, Faruque; Begum, Tahamina; Yusoff, Nasir (International Journal of Engineering and Technology, 2018)
Background: The other-race categorisation advantage (ORCA) is a well-established phenomenon, whereby other-race faces are categorised faster than own race faces. Objectives: This study investigated whether extraverts would demonstrate an ORCA-like effect toward unfamiliar other-race faces and familiar other-race faces in a modified oddball and choice reaction paradigm.Â Methods: This event-related potential (ERP) study employed a repeated measures experimental design with one independent variable (racial familiarity) and three levels (familiar other-race/Malay faces, unfamiliar other-race/African faces, control group/furniture photos). In the oddball task, African faces and Malay faces were the target stimuli and furniture photos were the standard stimuli. Electroencephalography data (EEG) was collected during the oddball task, from which ERP components were derived. Results: The reaction time (RT) for African and Malay faces were not significantly different.Â Significant effect of racial familiarity on P300 latencies at all electrode sites was not observed.Â However, there was a significant effect of racial familiarity on P300 amplitudes at midline electrodes (Cz).Â It was also observed that the P300 amplitude was larger for African faces than Malay faces at midline electrodes (Cz). Conclusion: An ORCA-like effect was not found in categorisation tasks involving faces from a familiar and an unfamiliar other-race, but a larger P300 amplitude was evoked by African faces. This dissociation between RT and P300 amplitude provided important theoretical implications with regard to models associated with ORCA. Specifically, the current findings lent support to the social cognition model and the Categorisation-Individuation Model (CIM).